Learning in cultural projects : case study of the outcomes of EU culture programme projects - Fredriksson, Johanna (Sibelius-Akatemia, 2013)
The aim of this study is to describe the outcomes of cultural projects and the learning generated from the projects. The learning is explored through outcomes in EU Culture Programme projects. The theoretical frame applied in this thesis, is based on different perspectives on projects and management theory. Additionally, the theoretical emphasis is put on organisational learning including project-based learning. This thesis is qualitative case study research, using focused interviews as a data collection method. The data is analysed through a content analysis method. The research shows that evaluation of project outcomes needs to be examined from a broad perspective, regarding both project and organisational factors. The study demonstrates interdependence between the project and the organisation. Furthermore, the research shows that projects are conducive to learning in organisations. The research describes a learning process, where the organisations implemented learnt practices in the project or/and outside the project. Additionally, obstacles for learning in form of a mismatch between project practices and main activities in the organisation were found.
Keywords: projektit; johtaminen; EU-ohjelmat; kulttuuri; oppiminen; fi=taidehallinto|sv=Arts Management|en=Arts Management|